β-arrestin1-E2F1-ac axis regulates physiological apoptosis and cell cycle exit in cellular models of early postnatal cerebellum - Abballe, Luana; Alfano, Vincenzo; Antonacci, Celeste; Cefalo, Maria Giuseppina; Cacchione, Antonella; Del Baldo, Giada; Pezzullo, Marco; Po, Agnese; Moretti, Marta; Mastronuzzi, Angela; De Smaele, Enrico; Ferretti, Elisabetta; et al. (Frontiers in Cell and Developmental Biology, 2023)
Development of the cerebellum is characterized by rapid proliferation of cerebellar granule cell precursors (GCPs) induced by paracrine stimulation of Sonic hedgehog (Shh) signaling from Purkinje cells, in the external granular layer (EGL). Then, GCPs differentiate and migrate into the inner granular layer (IGL) of the cerebellum to form a terminally differentiated cell compartment. Aberrant activation of Shh signaling leads to GCPs hyperproliferation and the onset of Shh medulloblastoma (MB), the most common embryonal brain tumor. β-arrestin1 (ARRB1) protein plays an important role downstream of Smoothened, a component of the Shh pathway. In the MB context, ARRB1 is involved in a regulatory axis in association with the acetyltransferase P300, leading to the acetylated form of the transcription factor E2F1 (Ac-E2F1) and redirecting its activity toward pro-apoptotic gene targets. This axis in the GCPs physiological context has not been investigated yet. In this study, we demonstrate that ARRB1 has antiproliferative and pro-apoptotic functions in cerebellar development. ARRB1 silencing increases proliferation of Shh treated-cerebellar precursor cells while decreases the transcription of E2F1-ac pro-apoptotic targets genes, thus impairing apoptosis. Indeed, chromatin immunoprecipitation experiments show a direct interaction between ARRB1 and the promoter regions of the pro-apoptotic E2F1 target gene and P27, indicating the double role of ARRB1 in controlling apoptosis and cell cycle exit in a physiological context. Our data elucidate the role of ARRB1 in the early postnatal stages of cerebellar development, in those cell compartments that give rise to MB. This series of experiments suggests that the physiological function of ARRB1 in neuronal progenitors is to directly control, cooperating with E2F1 acetylated form, transcription of pro-apoptotic genes.